Total Synthesis of (±)‐Dihydroisosubamol. Issue 5 (23rd December 2016) - Pflästerer, Daniel; Rudolph, Matthias; Yates, Brian F.; Ariafard, Alireza; Hashmi, A. Stephen K.
Abstract: We herein report the first total synthesis of the dibenzocycloheptanoide (±)‐dihydroisosubamol. The key step includes a recently developed gold‐catalysed hydroarylation reaction for the construction of the dibenzocycloheptene motif. Additional steps are a Suzuki‐Miyaura cross coupling, a palladium‐catalysed hydroxylation and an allylic oxidation. To access the saturated seven‐membered ring system an iridium‐catalysed hydrogenation proved to be successful. Abstract :